Growth behavior and temporal enterotoxin D expression of Staphylococcus aureus strains under glucose and lactic acid stress. (April 2016) - Sihto, Henna-Maria; Tasara, Taurai; Stephan, Roger; Johler, Sophia
Abstract: Ingestion of the staphylococcal enterotoxin D (SED) leads to staphylococcal food poisoning, the most prevalent foodborne intoxication worldwide. Patients suffer from acute signs of gastroenteritis such as violent vomiting, diarrhea, cramps, and fever. As the symptoms result in pronounced electrolyte imbalances and dehydration, the intoxication is particularly dangerous to children and the elderly. SED is formed during growth of Staphylococcus aureus in food. While growth of S. aureus is repressed by competing bacteria in most food matrices, the organism exhibits a crucial competitive growth advantage in foods with low pH or a low aw value ( e.g. through high sugar concentrations). To date, the effect of these stress conditions on sed expression is unclear. The objective of this study was to determine sed mRNA expression levels of S. aureus exposed to glucose and lactic acid stress conditions similar to food production and preservation. To this end, temporal sed mRNA expression levels of three S. aureus strains grown at control conditions, glucose stress conditions (30% glucose), and lactic acid stress conditions (pH 6.0) were determined using quantitative Real-Time PCR. Under both glucose and acid stress conditions, the mean lag phase duration was prolonged and maximum cell density in late stationary phase was decreased. In addition, glucose stress slightly increased the growth rate of the tested strains and led to decreased sed expression in late stationary phase. Lactic acid stress had no statistically significant effect on sed expression. Our study provides data on the effect of critical food-related stressors on growth and SE expression of S. aureus, which can be used for risk assessment. Highlights: Glucose stress (30%) can lead to decreased sed expression in stationary phase. Glucose stress leads to a slightly increased growth rate in Staphylococcus aureus . Lactic acid stress (pH 6.0) does not have a significant effect on sed expression.